2005
DOI: 10.1124/dmd.105.006197
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pregnane X Receptor in 2-Acetylaminofluorene-Mediated Induction of Drug Transport and -Metabolizing Enzymes in Mice

Abstract: ABSTRACT:Activation of the pregnane X receptor (PXR) mediates the induction of several drug transporters and -metabolizing enzymes. In vitro studies have reported that several of these genes are induced after exposure to the hepatocarcinogen, 2-acetylaminofluorene (2-AAF). Thus, we hypothesized that PXR may play a role in the in vivo induction of gene expression by 2-AAF. We examined the expression of the drug-metabolizing enzymes CYP1A2 and CYP3A11 and the drug transporters breast cancer resistance protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…These results confirm in vitro results showing that hypoxia reduces the sensitivity of EMT6/Ro cells to doxorubicin (Adriamycin), 5-fluorouracil, and actinomycin D because of an amplification of the P-glycoprotein gene family (Sakata et al, 1991). Induction of P-glycoprotein as well as BCRP and the organic anion-transporting polypeptide 2 (OATP2) frequently occurs through activation of PXR (Anapolsky et al, 2006); however, this mechanism did not appear to play an important role in hypoxic animals because mRNA levels of BCRP and OATP2 as well as PXR were not affected. Alternatively it is plausible that binding sites for HIF-1, found on the promoter region of MDR1 (Krishnamurthy et al, 2004), may be involved in the observed hypoxia-mediated induction of P-glycoprotein.…”
supporting
confidence: 77%
“…These results confirm in vitro results showing that hypoxia reduces the sensitivity of EMT6/Ro cells to doxorubicin (Adriamycin), 5-fluorouracil, and actinomycin D because of an amplification of the P-glycoprotein gene family (Sakata et al, 1991). Induction of P-glycoprotein as well as BCRP and the organic anion-transporting polypeptide 2 (OATP2) frequently occurs through activation of PXR (Anapolsky et al, 2006); however, this mechanism did not appear to play an important role in hypoxic animals because mRNA levels of BCRP and OATP2 as well as PXR were not affected. Alternatively it is plausible that binding sites for HIF-1, found on the promoter region of MDR1 (Krishnamurthy et al, 2004), may be involved in the observed hypoxia-mediated induction of P-glycoprotein.…”
supporting
confidence: 77%
“…The impact of PXR activation on the regulation of transporters in placenta was further assessed in pregnant wild-type and knockout mice. Activation of PXR has been shown to significantly induce the hepatic expression of Cyp3a11, Oatp2, and several of the ABC drug transporters including Mdr1, Mrp2, and Mrp3 in nonpregnant mice (Teng and Piquette-Miller, 2005;Anapolsky et al, 2006). Likewise, PCN-mediated induction of several PXR gene targets has been reported in the intestine and blood-brain barrier (Bauer et al, 2004;Cheng and Klaassen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, largely due to increasing hormonal levels, the hepatic expression of PXR increases by approximately 20-fold during the perinatal period in mice (Masuyama et al, 2001). PXR-mediated induction of Cyp3a and several key ABC drug efflux transporters in liver such as Mdr1, Mrp2, Mrp3, and Bcrp has been demonstrated (Guo et al, 2002;Kliewer et al, 2002;Teng et al, 2003;Anapolsky et al, 2006). Likewise, PXR activation has been found to induce expression and activity of P-gp at the blood-brain barrier (Bauer et al, 2004(Bauer et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that this sequence also interacts with PXR and the constitutive androstane receptor. Indeed, most of the PXR ligands such as rifampicin and hyperforin have been shown to upregulate MRP2 expression in humans, mice, and rats (Fromm et al 2000, Kast et al 2002, Anapolsky et al 2006. Excess glucocorticoid concentrations increase the MRP2 mRNA levels, which implicates glucocorticoidinducible PXR activation (Kliewer et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…2A), which suggests that the induction of MRP2 in the TAM-resistant breast cancer cells is mediated through the transcriptional activation of the MRP2 gene. Since PXR is believed to be an essential transcription factor for the induction of MRP2 (Teng & Piquette-Miller 2005), and the roles of PXR in the inducible expression of MRP2 have been examined extensively (Kast et al 2002, Anapolsky et al 2006, this study compared the reporter activities in both MCF-7 and TAMR-MCF-7 cells using the PXR reporter plasmid (three copies of the PXR-responsive elements from CYP3A23 gene; Kast et al 2002). The reporter activity was significantly higher in the TAMR-MCF-7 cells than in the control MCF-7 cells (Fig.…”
Section: Involvement Of Pxr In the Enhanced Mrp2 Expression In Tam-rementioning
confidence: 99%